(untitled) - The World Bank (Washington, D.C., 2009)
Now in its eigth edition, this pocket-sized reference on key development data for over 200 countries provides profiles of each country with 54 development indicators about people, environment, economy, technology and infrastructure, trade, and finance.
Keywords: Developing countries,Phát triển quốc gia; Socio-economic aspects,Khía cạnh kinh tế xã hội